Enzyme display technology for lignocellulosic biomass valorization by yeast cell factories - Bamba, Takahiro; Guirimand, Gregory; Kondo, Akihiko; Hasunuma, Tomohisa (Current opinion in green and sustainable chemistry, 2022)
Metabolic engineering allows the implementation and development of more and more efficient microbial cell factories, able to produce numerous valuable compounds, including ethanol, from various feedstocks. The valorization of lignocellulosic materials coming from agricultural wastes constitutes a promising way to achieve a more sustainable society. Whole-cell biocatalysts (WCBs) such as yeast cell factories displaying enzymes directly on their cell surface are valuable tools to achieve this goal. In recent decades, cell surface display technology in yeast has made impressive progress in this direction. This review will provide the reader with a timely overview of the recent achievements in the field, including the rising of non-conventional yeast strains as promising chassis for the valorization of lignocellulosic biomass by WCBs. •Bio-production of valuable compounds is a promising alternative to chemical processes.•Yeasts are valuable platforms for bioconversion of lignocellulosic biomass.•Enzyme display technology enabled the development of efficient yeast cell factories.•Non-conventional yeasts are promising chassis for whole-cell biocatalysis.•Valorization of lignocellulosic biomass by arming yeasts is a sustainable solution. [Display omitted]